Histological study of the licorice extract as Phytoestrogens, compared with pregnant mare serum gonadotrophyin hormone (PMSG) in the female Reproductive system of Awassi ewes: Abbas, H. N . ; AL-timemy, A .H. ; Saffaa, A. B. - N ., Abbas H. (The Iraqi Journal of Veterinary Medicine, 2010)
This study was carried out at the Iraqi ministry of science & Technology as well as the Vet. Collage- Baghdad. This research aimed to study the effects of macroscopic and histological licorice extract in the genital tract of ewes as well as to study the effect of the extract on reproductive efficiency to be compared with serum hormone PMSG( pregnant horse) used for this purpose. The study used (36) local ewes which are divided into three equal groups (T 1, T 2, T 3) (Licorice extract 300, PMSG 500 and zero respectively), The first group( T1) of ewes was given licorice extract a single dose of 300 mg / kg body weight weekly for a period of ( 6) weeks, The second group (T 2), they were treated with hormone PMSG with a dose of 500 unit by intramuscular injection on the day of the raising of the vaginal sponges. As for the third group (T 3) which was given normal saline only it was used as a control group .The study results that the use of licorice extract as (Phytoestrogens) leads to a lack of awareness of the pathological changes on tissue of the genital tract of treated ewes or reduction of fertility and reproductive efficiency. As the study showed that the fertility rate increased ( 1,5%) in the Group of licorice extract which is similar to the group PMSG compared with control group which had a 1.0 fertility rate and a proportion of 88,8% of fertility. In conclusion, the licorice extract could be used to raise the rates of certain reproductive efficiency in sheep without causing any satisfactory damage in the canal genital ewes or reduction to the reproductive efficiency